Coarse‐grained deltas approaching shallow‐water canyon heads: A case study from the Lower Pleistocene Messina Strait, Southern Italy. Issue 6 (25th May 2021) - Longhitano, Sergio G.; Chiarella, Domenico; Gugliotta, Marcello; Ventra, Dario
Abstract: The tide‐dominated Messina Strait (southern Italy) is a 3 km wide marine passageway, whose block‐faulted borders form steep subaqueous zones incised by canyons and gullies. These erosional features retreat towards the shorelines and are often in direct connection with subaerial valley‐bounded river deltas. High‐energy density‐flows generated by river floods periodically enter the canyon heads, attaining supercritical‐flow regime and accreting large, upslope‐migrating bedforms. Although these bedforms have been documented in recent studies, little attention has been paid to the definition of the type of delta entering canyon heads, the internal features of river‐influenced deposits accumulated in the nearshore zone, and their interplay with tidal currents flowing axially to the strait. This study focuses on a Lower Pleistocene coarse‐grained succession exposed along the north‐eastern margin of the modern Messina Strait, investigated using conventional facies analysis and sedimentological logging, integrated with photogrammetric techniques and interpretation of drone‐acquired imagery. Facies confinement between basement blocks suggests a subaqueous delta complex shed from the tectonically controlled margin of the ancient strait and entering shallowly submerged canyon heads. Basal breccias, conglomerates and pebbly sandstones exhibiting channel‐form discontinuities and upslope dipping backsets are interpreted as cyclic‐step and antidune deposits. Units composed of these facies are comprised between master erosional surfaces and tidal ravinement surfaces. The tidal ravinements suggest that canyon infill occurred during a major phase of sea‐level rise, punctuated by minor falls and stillstands. These surfaces are overlain by mixed bioclastic–siliciclastic, arenitic, trough and planar cross‐strata, representing dunes migrating roughly parallel to the palaeo‐coastline and originated by tidal currents amplified by the narrowing of the ancient Messina Strait. Tidal‐influenced sedimentation dominated over the fluvial‐influenced processes during the late transgression, overfilling the canyon relief. The exceptionally good exposure of depositional architectures and facies characteristics is key to outline the general features of a specific type of delta system, fed by valley‐bounded rivers and entering canyon heads in the nearshore of tectonically‐controlled, tide‐influenced steep strait margins. The pre‐existing subaqueous incised topography forced the delta front to be split into lobe branches during the canyon infilling, hampering clinoform architectures and preserving large supercritical‐flow sedimentary structures. This study suggests these as possible criteria for the recognition of similar systems in outcrop or subsurface.